Numerical simulation analysis of controlling settlement by water-resisting curtain combined with recharge in deep foundation pit - Xu, Xubing; Zheng, Yonglai; Lan, Xin; Pan, Jie; Wen, Yuan (Journal of Civil Engineering and Management, 2024)
This study takes a nearby foundation pit project of a high-speed railway in Yancheng City, Jiangsu Province as an example to investigate the impact of deep foundation pit projects on groundwater and the surrounding environment. Through on-site monitoring, in-situ testing, and numerical simulation, we conducted a comprehensive study of the impact of foundation pit projects on groundwater and the surrounding environment. The evolution of groundwater levels and surface displacement during the excavation of foundation pits was analyzed, and a method for measuring the permeability of target soil layers in situ was studied. The simulation of recharge under various soil conditions was performed, and the outcomes demonstrated the effective isolation of hydraulic connections between the interior and exterior of the foundation pit by the water-resistant curtain. Precipitation head and constant head recharging tests were employed to ascertain the actual permeability. The characteristic time method calculation exhibited remarkable efficiency and accuracy in determining the permeability coefficient of the recharging soil layer. Recharging phreatic and confined water layers has differing degrees of influence on surface deformation, with the impact of confined water layers requiring more time to stabilize. These findings contribute significantly to a more comprehensive understanding of the environmental repercussions associated with deep excavation projects, thereby enhancing safety and environmental protection measures in excavation construction practices.